Optimización del proceso de fabricación de postes de hormigón armado en DISPOSTES CIA. LTDA. - Cayo León, Jhonatan Fabricio (2021)
The company DISPOSTES CIA. LTDA has as it’s main activity the manufacture of concrete poles that has positioned itself radically in the market, despite having few years of competition in it. However, growth and innovation must be constant in the face of competition. Therefore, it is essential to have a time study of the production area, which is why this project is focused on it, applying a descriptive research and using the inductive method to determine the activities performed in the areas that require analysis for further optimization. It is necessary to identify all the processes through a general flow diagram and a route diagram to have a clear idea of how a concrete pole is made; in addition, an analytical flowchart presents the specific activities. The fundamental pillar of the project lies in the time study once the process in general and the areas of analysis have been identified, taking into account key factors such as the valuation of the rhythm, the basic time and the supplements to finally obtain the standard time that in turn allows to determine the current capacity of the plant. Finally, after the study and its respective analysis, an improvement is proposed by eliminating or combining certain activities, defining a new plant layout and proposing a new method, thus optimizing and increasing production rates with the same resources currently available.